2022
DOI: 10.1038/s41598-021-04515-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and lifestyle factors in relation to senile cataract: a Mendelian randomization study

Abstract: We conducted a Mendelian randomization study to determine the associations of body mass index (BMI), type 2 diabetes (T2D), systolic blood pressure (SBP), coffee and alcohol consumption and smoking initiation with senile cataract. Independent single nucleotide polymorphisms associated with the metabolic and lifestyle factors at the p < 5 × 10–8 were selected as instrument variables. Summary-level data for senile cataract were obtained from the FinnGen consortium (20,157 cases and 154,905 non-cases) and UK B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
3
24
2
1
Order By: Relevance
“…After exclusion of studies using overlapping or same outcome data, 29 articles based on non-overlapping populations were eligible for inclusion in one or more meta-analyses. The number of studies included in each outcome category was seven for circulatory system diseases, 4 , 5 , 6 , 7 , 8 , 9 , 10 six for digestive system diseases, 11 , 12 , 13 , 14 , 15 , 16 six for nervous system diseases, 17 , 18 , 19 , 20 , 21 three for musculoskeletal system outcomes, 22 , 23 , 24 two for endocrine and metabolic diseases, 25 , 26 two for eye diseases, 27 , 28 and four for neoplasms. 29 , 30 , 31 , 32 In addition to the included studies, 123 de novo MR analyses ( n =51 for smoking initiation, n = 72 for lifetime smoking) were conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After exclusion of studies using overlapping or same outcome data, 29 articles based on non-overlapping populations were eligible for inclusion in one or more meta-analyses. The number of studies included in each outcome category was seven for circulatory system diseases, 4 , 5 , 6 , 7 , 8 , 9 , 10 six for digestive system diseases, 11 , 12 , 13 , 14 , 15 , 16 six for nervous system diseases, 17 , 18 , 19 , 20 , 21 three for musculoskeletal system outcomes, 22 , 23 , 24 two for endocrine and metabolic diseases, 25 , 26 two for eye diseases, 27 , 28 and four for neoplasms. 29 , 30 , 31 , 32 In addition to the included studies, 123 de novo MR analyses ( n =51 for smoking initiation, n = 72 for lifetime smoking) were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…During the last few years, the potential causal association between smoking and risk of different diseases has been investigated using the Mendelian randomization (MR) approach. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 MR is a method that utilizes genetic variants associated with a difference in the exposure (e.g., smoking liability) as instrumental variable for the exposure to determine the causal role of the exposure in the development of disease. 33 The MR design mitigates confounding because genetic alleles are randomly allocated when passed from parents to offspring and therefore usually not related to other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the participants in this study were in high cardiovascular risk (e.g., with a high prevalence of diabetes, hypercholesterolemia, and hypertension) [38], which is different from the UK Biobank individuals with a generally good health status. Our recent MR study found causal associations of several cardiovascular risk factors with an increased risk of cataract [39]. In the PREvención con DIeta MEDiterránea Study, participants with at least one cardiovascular risk factor were at a high risk of cataract.…”
Section: Discussionmentioning
confidence: 96%
“…In 2022, it was genetically predicted that coffee consumption showed a suggestive association with senile cataract [ 38 ]. In two studies, it was found that higher coffee consumption was associated with a higher risk of primary open-angle glaucoma (POAG) and open-angle glaucoma (OAG) compared with those who did not drink coffee [ 39 , 40 ].…”
Section: The Impact Of Coffee During Pregnancy and In Diseasesmentioning
confidence: 99%